TRAF6 Is Essential for Maintenance of Regulatory T Cells That Suppress Th2 Type Autoimmunity - Muto, Go (Public Library of Science, 2013)
Regulatory T cells (Tregs) maintain immune homeostasis by limiting inflammatory responses. TRAF6 plays a key role in the regulation of innate and adaptive immunity by mediating signals from various receptors including the T-cell receptor (TCR). T cell-specific deletion of TRAF6 has been shown to induce multiorgan inflammatory disease, but the role of TRAF6 in Tregs remains to be investigated. Here, we generated Treg-specific TRAF6-deficient mice using Foxp3-Cre and TRAF6-flox mice. Treg-specific TRAF6-deficient (cKO) mice developed allergic skin diseases, arthritis, lymphadenopathy and hyper IgE phenotypes. Although TRAF6-deficient Tregs possess similar in vitro suppression activity compared to wild-type Tregs, TRAF6-deficient Tregs did not suppress colitis in lymphopenic mice very efficiently due to reduced number of Foxp3-positive cells. In addition, the fraction of TRAF6-deficient Tregs was reduced compared with wild-type Tregs in female cKO mice without inflammation. Moreover, adoptive transfer of Foxp3 (+) Tregs into Rag2(-/-) mice revealed that TRAF6-deficient Tregs converted into Foxp3(-) cells more rapidly than WT Tregs under lymphopenic conditions. Fate-mapping analysis also revealed that conversion of Tregs from Foxp3(+) to Foxp3(-) (exFoxp3 cells) was accelerated in TRAF6-deficient Tregs. These data indicate that TRAF6 in Tregs plays important roles in the maintenance of Foxp3 in Tregs and in the suppression of pathogenic Th2 type conversion of Tregs.